2007
DOI: 10.1128/aac.01459-06
|View full text |Cite
|
Sign up to set email alerts
|

Roxithromycin Favorably Modifies the Initial Phase of Resistance against Infection with Macrolide-Resistant Streptococcus pneumoniae in a Murine Pneumonia Model

Abstract: Sub-MIC levels of macrolides down-regulate bacterial virulence factors and suppress inflammatory processes. The ability of macrolides to reduce the production of pneumolysin has been shown to explain the discrepancy between in vitro resistance and outcomes with macrolides against macrolide-resistant Streptococcus pneumoniae. In this study, we determined whether the ability of macrolides to regulate inflammatory processes is beneficial for innate resistance to macrolide-resistant pneumococci in a murine pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Pneumococcal pneumonia was induced by intratracheal inoculation of type 3 S. pneumoniae strain NMU112 in a 20-l volume (5 ϫ 10 4 cfu, equivalent to 100 LD50) as previously described (62). The exact inoculated dose was verified by plating out 500ϳ1,000-fold dilutions onto blood agar plates.…”
Section: Infection With S Pneumoniamentioning
confidence: 99%
“…Pneumococcal pneumonia was induced by intratracheal inoculation of type 3 S. pneumoniae strain NMU112 in a 20-l volume (5 ϫ 10 4 cfu, equivalent to 100 LD50) as previously described (62). The exact inoculated dose was verified by plating out 500ϳ1,000-fold dilutions onto blood agar plates.…”
Section: Infection With S Pneumoniamentioning
confidence: 99%
“…All macrolide antibiotics impair bacterial protein synthesis by acting on the 50S bacterial ribosomal subunit. Macrolides at subinhibitory concentrations, but not other groups of antibiotics, inhibit the production of pneumolysin, which is an important virulence factor of S. pneumoniae involved in evasion of C3b (1,10,24,25). In addition, it has been shown that macrolide compounds, such as ERY, AZM, and clarithromycin, but not roxithromycin, significantly inhibited pneumolysin and PspA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a reduction in the number of PMNs, bacterial counts were lower in treated mice. This was attributed to an increase in mononuclear cells that exhibit enhanced phagocytic bactericidal activity targeted against pneumococci and cause less damage to surrounding lung tissue [57]. In addition to the effect on cytokines and inflammatory cells, effects of macrolides on structural cells of the respiratory tract have also been reported.…”
Section: Macrolide Antibioticsmentioning
confidence: 96%